Malat1 deficiency prevents hypoxia-induced lung dysfunction by protecting the access to alveoli - Sallé-Lefort, Sandrine; Miard, Stéphanie; Henry, Cyndi; Arias-Reyes, Christian; Marcouiller, François; Beaulieu, Marie-Josée; Aubin, Sophie; Lechasseur, Ariane; Jubinville, Éric; Marsolais, David; Morissette, Mathieu C.; Joseph, Vincent; et al. (Frontiers in Physiology, 2022)
Hypoxia is common in lung diseases and a potent stimulator of the long non-coding RNA Metastasis-Associated Lung Adenocarcinoma Transcript 1 (MALAT1). Herein, we investigated the impact of Malat1 on hypoxia-induced lung dysfunction in mice. Malat1-deficient mice and their wild-type littermates were tested after 8 days of normoxia or hypoxia (10% oxygen). Hypoxia decreased elastance of the lung by increasing lung volume and caused in vivo hyperresponsiveness to methacholine without altering the contraction of airway smooth muscle. Malat1 deficiency also modestly decreased lung elastance but only when tested at low lung volumes and without altering lung volume and airway smooth muscle contraction. The in vivo responsiveness to methacholine was also attenuated by Malat1 deficiency, at least when elastance, a readout sensitive to small airway closure, was used to assess the response. More impressively, in vivo hyperresponsiveness to methacholine caused by hypoxia was virtually absent in Malat1-deficient mice, especially when hysteresivity, a readout sensitive to small airway narrowing heterogeneity, was used to assess the response. Malat1 deficiency also increased the coefficient of oxygen extraction and decreased ventilation in conscious mice, suggesting improvements in gas exchange and in clinical signs of respiratory distress during natural breathing. Combined with a lower elastance at low lung volumes at baseline, as well as a decreased propensity for small airway closure and narrowing heterogeneity during a methacholine challenge, these findings represent compiling evidence suggesting that the lack of Malat1 protects the access to alveoli for air entering the lung.